Nota sobre novo caso autóctone de tripanossomíase americana no litoral Sul do Estado de São Paulo, Brasil A new case of American trypanosomiasis in the Southern Coastal Region of S. Paulo State, Brazil - Oswaldo Paulo Forattini; Eduardo Olavo da Rocha e Silva; José Maria Soares Barata; Elias Boainain (Universidade de São Paulo, 1981)
Descreve-se novo caso autóctone de tripanossomíase americana no litoral Sul do Estado de São Paulo, Brasil. De maneira semelhante à nota anterior, as evidências sugerem a transmissão por contaminação no manuseio de carcaças de mamíferos silvestres utilizados na alimentação. Este achado confirma a hipótese da existência de nível endêmico regional. A new indigenous case of American trypanosomiasis in the Southern Coastal Region of the State of S. Paulo, Brazil is reported. Similary with the first one, reported elsewhere, no triatomianae bugs were be involved and so contamination through handling of wild mammals carcasses seems to be a suitable transmission mechanism. This finding sustain the existence of a regional endemic pattern.